Power Quality Enhancement of Integration Photovoltaic Generator to Grid under Variable Solar Irradiance Level using MPPT-Fuzzy - Amirullah Amirullah; Agus Kiswantono (Institute of Advanced Engineering and Science, 2016)
The paper presents power quality enhancement on low voltage of three phase grid caused by PV generator integration under variabel solar irradiance level on constant temperature and load. MPPT Fuzzy helps to generate duty cycle to control DC/DC boost converter of PV generators. This model was expected to improve power quality due to unbalance voltage and current, low voltage and current harmonics, and low input power factor. There were eigth scenarios PV generator connected to three phase grid using MPPT Fuzzy and compared with MPPT P and O. The research results that application of two methods on different irradiance and PV generator integration level produces unbalanced voltage value stable at 0%. At the same conditions, the use of MPPT Fuzzy results unbalanced current was greater than MPPT P and O. On solar irradiance level fixed, the greater number of PV generator connected to three-phase grid, then value of average voltage and current harmonics (THD) will increases. At the level of solar radiation increases, average grid voltage and current THD also have increased. The average grid voltage and current THD was reduced after using MPPT Fuzzy. The application of MPPT Fuzzy was able to enhance profile of grid voltage and current THD due to integration of a number of PV generator to three phase grid corresponding with IEEE Standard 519-1992. MPPT Fuzzy was capable to improve input power factor better than MPPT P and O.